Degradable waterproof and oilproof paper pulp molded product and preparation method thereof

By pretreating and modifying polyhydroxybutyrate and starch, combined with the use of modified montmorillonite, the problem of insufficient waterproof and oil-proofing performance of pulp molded products is solved, and efficient waterproofing and oil-proofing and good mechanical properties are achieved.

CN119824732APending Publication Date: 2025-04-15DONGGUAN POLYTECHNIC

Patent Information

Application Number
CN202510149094.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing pulp molded products have shortcomings in waterproof and oil-resistant properties, and the polar hydroxyl groups of its main component cellulose are prone to adsorbing water molecules, resulting in performance not meeting the requirements.

Method used

By pulverizing and pretreating the polyhydroxybutyrate, the ester bond rupture on its surface is increased, thereby improving its reactivity with modified starch. At the same time, the modified starch is introduced by ball milling and etherification reaction to improve its hydrophobicity. Modified montmorillonite is introduced through intercalation reaction and silane groups to improve its dispersion and hydrophobicity, and works in concert with modified starch-coated polyhydroxybutyrate to enhance the waterproof and oil-resistant properties of pulp molded products.

Benefits of technology

It significantly improves the waterproof and oil-resistant properties of pulp molded products, while ensuring their mechanical strength and overall quality, avoiding the use of fluorine-containing compounds, and ensuring environmental protection and health.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a degradable waterproof and oilproof paper pulp molded product and a preparation method thereof. The preparation method comprises the following steps: S1, pretreatment of polyhydroxybutyrate; s2, preparing modified starch; s3, coating the polyhydroxybutyrate with the modified starch; s4, preparation of modified montmorillonite; and S5, preparing the paper pulp molded product. According to the paper pulp molded product, the degradable oleophobic and hydrophobic high polymer material polyhydroxybutyrate is introduced, the degradability of the paper pulp molded product is guaranteed, the waterproof and oil-proof performance of the paper pulp molded product is improved, the polyhydroxybutyrate is coated with the modified starch, the compatibility of the polyhydroxybutyrate and paper pulp fibers is improved, and the paper pulp molded product has the advantages of being environmentally friendly and free of pollution. The overall quality of a paper pulp molded product is ensured; meanwhile, the added modified montmorillonite and the modified starch coated polyhydroxybutyrate can synergistically improve the barrier property of a paper pulp molded product, and the waterproof and oil-proof properties of the paper pulp molded product are jointly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pulp molding, and in particular relates to a degradable, waterproof and oil-proof pulp molding product and a preparation method thereof. Background Art

[0002] Plastic is a high-cost-effective polymer compound that has been deeply integrated into all aspects of our production and life, becoming the most common type of material in the daily production and life of all mankind. Compared with other materials, plastic has obvious advantages in processing, performance and cost, and is widely used in many industries such as agriculture, product packaging, construction materials, transportation, electrical and electronic, and daily necessities. However, the increasing accumulation of plastic waste is difficult to degrade in the natural environment, especially disposable plastic products with large usage and extremely low recycling rate, which seriously damage the earth's soil environment, marine environment and atmospheric environment.

[0003] Under the general trend of global plastic ban and restriction, paper-based packaging materials are increasingly valued by people. Their raw materials have a wide range of sources and excellent biocompatibility. The waste of paper-based packaging materials can be recycled and regenerated by waste paper pulping process to improve resource utilization, and can be degraded into harmless substances by microorganisms under natural environmental conditions. All of the above shows that paper-based packaging materials fully meet the concept of "green packaging" stipulated by the packaging industry. Therefore, paper-based products can completely replace plastic products and become new packaging materials in the future.

[0004] Pulp molding packaging materials refer to materials that use primary plant fibers or recycled fibers from waste paper as the main raw materials. When pulp molding is made, chemical additives with different functions are first selected according to different performance requirements; then the chemical additives are added to the pulp suspension and fully mixed, and a wet paper mold is formed through a special mold forming machine, which is demolded, dehydrated and dried; finally, a paper product with a specific geometric cavity structure and certain support and cushioning properties is formed through a finishing process. The addition of chemical additives can make pulp molded products have excellent mechanical and performance, and the raw materials of pulp molded products are cheap and easy to obtain, the technical process is simple and environmentally friendly, and the waste can be recycled. In recent years, due to its low price, easy processing, and wide source of raw materials, it has been widely used in the packaging field as a substitute for foamed plastics.

[0005] Although pulp molded products are gradually replacing plastic packaging, they cannot completely replace plastic packaging due to their shortcomings such as powdering, chipping, poor mechanical strength and poor waterproof and oil-proof properties. The fundamental reason for this phenomenon is that the main component of pulp molded products is cellulose, and there are many gaps in the fiber network. At the same time, the polar hydroxyl groups of cellulose easily adsorb water molecules, so that the performance of pulp molded products does not meet the use requirements. The invention patent of Chinese patent application CN115821641A discloses a paper fiber molding material and a preparation method thereof, including a paper fiber layer and a first functional layer and a second functional layer respectively arranged on the two side surfaces of the paper fiber layer. By arranging the functional layers on the upper and lower surfaces of the paper fiber layer, the type of functional layer can be selected according to actual needs, so as to facilitate the realization of waterproof, anti-corrosion, oil-proof and impact-proof functions; however, since the arranged functional layer is directly in contact with the external environment, it is greatly affected by external factors, resulting in the functional layer being easily damaged, thereby affecting the functional effect, resulting in the functional effect of the pulp molding material not being durable. Chinese patent application CN113215862A discloses a method for preparing a fully biodegradable fluorine-free pulp molded dinner plate, wherein pulp raw materials are crushed to obtain slurry, the processed slurry is passed through a deflaker to obtain a uniform slurry, and then auxiliary agents such as a waterproofing agent, a wet strength agent, and a dry strength agent are added to obtain a mixed slurry; after being sent into a dinner plate forming machine, a wet dinner plate blank is obtained, and a mixed solution of nano zinc oxide, ethanol, and stearic acid is sprayed on the wet dinner plate blank in succession, and finally the wet dinner plate blank is dehydrated, hot-pressed, and trimmed to obtain a finished dinner plate, giving the pulp molding a certain waterproof and oil-proof property, but the waterproof and oil-proof property of the pulp molded product in this patent needs to be further improved. Summary of the invention

[0006] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a degradable, waterproof and oil-proof pulp molded product and a preparation method thereof. The pulp molded product has excellent waterproof and oil-proof properties and good mechanical strength, thereby ensuring the overall quality of the product. At the same time, since no fluorine-containing compounds are added, the harm to the human body and the environment after degradation of the pulp molded product is avoided, making it more environmentally friendly and healthy.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A method for preparing a degradable, waterproof and oil-proof pulp molded product comprises the following steps:

[0009] S1, crushing polyhydroxybutyrate to obtain micro-nano polyhydroxybutyrate powder, then adding the polyhydroxybutyrate powder into a sodium hydroxide solution for immersion treatment, filtering, washing and drying after the treatment to obtain pretreated polyhydroxybutyrate;

[0010] S2, ball-milling the starch to obtain pretreated starch; adding the pretreated starch to a sodium hydroxide solution for immersion treatment, adding 2,3-epoxypropyltrimethylammonium chloride after the treatment to carry out etherification reaction, adding anhydrous ethanol for precipitation after the reaction, washing, drying, and obtaining a solid product; then adding the solid product to DMF, followed by adding succinic anhydride and triethylamine, stirring for reaction, filtering, washing, and drying after the reaction to obtain modified starch;

[0011] S3, adding the modified starch in step S2 into deionized water, and then adding the pretreated polyhydroxybutyrate in step S1, stirring, and then performing reduced pressure rotary evaporation to obtain modified starch-coated polyhydroxybutyrate;

[0012] S4, adding montmorillonite to deionized water, then adding hexadecyltrimethylammonium bromide, stirring for reaction, filtering, washing, and drying after the reaction is completed to obtain composite montmorillonite; adding composite montmorillonite to ethanol aqueous solution, then adding vinyltriethoxysilane, heating for reaction, filtering, washing, and drying after the reaction is completed to obtain vinyl composite montmorillonite; adding vinyl composite montmorillonite to N,N-dimethylformamide, then adding 10-undecene-1-ol and azobisisobutyronitrile, carrying out constant temperature reaction, filtering, washing, and drying after the reaction is completed to obtain modified montmorillonite;

[0013] S5. After soaking the waste corrugated cardboard in water, introduce it into a pulper barrel for pulping for 20-30 minutes to prepare a pulp suspension with a solid content of 10-15%. Then, add the modified starch-coated polyhydroxybutyrate in step S3, the modified montmorillonite in step S4, a dispersant, and Span-80 to the pulp suspension for mixing and beating to obtain a mixed slurry, which is then introduced into a mold, filtered and extruded by a pulp molding machine, demolded, dried, and hot-pressed to obtain the biodegradable, waterproof, and oil-proof pulp molded product.

[0014] Preferably, the particle size of the polyhydroxybutyrate powder in step S1 is 20-30 μm; the concentration of the sodium hydroxide solution is 1-1.5 mol / L, the temperature of the immersion treatment is 50-60° C., and the time is 1-2 h.

[0015] In the present invention, polyhydroxybutyrate is pretreated by first crushing it to increase the specific surface area, and the crushed polyhydroxybutyrate can be filled into the gaps between pulp fibers during the mixing and beating process to increase the density of the fibers, thereby improving the waterproof and oil-proof properties of pulp molded products; then, it is treated with alkali to break the ester bonds on the surface of the polyhydroxybutyrate, thereby increasing the number of carboxyl groups and hydroxyl groups on the surface of the polyhydroxybutyrate, which is beneficial to the subsequent reaction with modified starch.

[0016] Preferably, the rotation speed of the ball mill in step S2 is 3000-4000 r / min, and the time is 30-50 min; the concentration of the sodium hydroxide solution is 0.5-0.8 mol / L, the temperature of the immersion treatment is 40-50°C, and the time is 30-40 min; the mass ratio of the pretreated starch and 2,3-epoxypropyltrimethylammonium chloride is 80-100:8-12, and the temperature of the etherification reaction is 60-70°C, and the time is 6-8 h.

[0017] In the present invention, firstly, ball milling is performed to destroy the hydrogen bonding between starch molecules under the action of shear force, thereby reducing the crystallinity of starch and increasing the internal energy of starch, thereby improving the reaction activity of starch; then, the pretreated starch is reacted with 2,3-epoxypropyltrimethylammonium chloride to introduce quaternary ammonium salt into starch, thereby improving the adhesion performance of starch ions to pulp fibers; then, the cationized starch is reacted with succinic anhydride to introduce hydrophobic alkyl groups into starch to improve the hydrophobicity of starch; this method introduces hydrophilic groups and hydrophobic groups into starch respectively through two-step reactions to obtain modified starch. Compared with the simultaneous introduction of hydrophilic groups and hydrophobic groups, the performance of starch derivatives can be changed by adjusting the content of hydrophilic groups and hydrophobic groups, thereby improving the bonding strength of starch to pretreated polyhydroxybutyrate and pulp fibers, thereby improving the mechanical properties of pulp molded products.

[0018] Preferably, in step S2, the mass ratio of the solid product, succinic anhydride and triethylamine is 80-100:8-12:40-50; the stirring reaction temperature is 70-80°C and the time is 4-6h.

[0019] Preferably, in step S3, the mass ratio of the modified starch to the pretreated polyhydroxybutyrate is 50-60:150-200, the stirring temperature is 60-70° C., and the stirring time is 2-3 h.

[0020] In the present invention, modified starch and pretreated polyhydroxybutyrate are stirred and coated, so that the pretreated polyhydroxybutyrate is coated with modified starch. Since the modified starch contains hydrophobic alkyl groups, the bonding strength between the pretreated polyhydroxybutyrate and the pulp fiber is improved.

[0021] Preferably, in step S4, the mass ratio of montmorillonite and hexadecyltrimethylammonium bromide is 50-60:6-9, the stirring reaction temperature is 70-80°C, and the time is 3-5h; the mass ratio of the composite montmorillonite and vinyltriethoxysilane is 50-60:5-8, the heating reaction temperature is 60-70°C, and the time is 1-2h.

[0022] In the present invention, montmorillonite is added as a filler into a pulp molded product. The montmorillonite is first subjected to an intercalation reaction with hexadecyltrimethylammonium bromide, which can increase the compatibility between the montmorillonite and the pulp fiber on the one hand, and increase the interlayer spacing of the montmorillonite on the other hand to improve the degree of exfoliation of the montmorillonite on the pulp fiber. The increased interlayer spacing is beneficial to the subsequent reaction. Subsequently, vinyltriethoxysilane is reacted with the composite montmorillonite, which improves the dispersibility of the montmorillonite on the one hand, and the introduced silane group can also improve the hydrophobicity and oleophobicity of the montmorillonite on the other hand. At the same time, double bonds are introduced into the composite montmorillonite, which is beneficial to the subsequent reaction.

[0023] Preferably, in step S4, the mass ratio of the vinyl composite montmorillonite, 10-undecene-1-ol, and azobisisobutyronitrile is 50-60:4.5-7:0.2-0.4 g, and the isothermal reaction temperature is 80-90° C. and the reaction time is 2-4 h.

[0024] In the present invention, 10-undecene-1-ol is introduced into the composite montmorillonite through a double bond addition reaction. 10-undecene-1-ol contains a long-chain alkyl group, which further improves the waterproof performance of the pulp molded product.

[0025] Preferably, in step S5, the mass ratio of the pulp suspension, modified starch-coated polyhydroxybutyrate, modified montmorillonite, dispersant, and Span-80 is 1000:50-60:30-40:3-6:5-10; and the dispersant is one or more of carboxymethyl cellulose, sodium hexamethyl phosphate, and sodium dodecylbenzene sulfonate.

[0026] Preferably, in step S5, the mixed slurry is filtered to a solid content of 50-55%, and then demolded after extrusion molding at a pressure of 5-15 MPa to obtain a pulp molded wet blank, and then the pulp molded wet blank is placed in a drying oven, dried at 80-90°C for 4-5 hours, and then transferred to a flat vulcanizer for hot pressing and shaping at 100-110°C and 7-10 MPa for 5-8 minutes.

[0027] The present invention also protects a degradable, waterproof and oil-proof pulp molded product prepared by the method as described above.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) The degradable, waterproof and oil-proof pulp molded product provided by the present invention introduces the degradable, oleophobic and hydrophobic polymer polyhydroxybutyrate into the pulp molded product, which not only ensures the degradability of the pulp molded product, but also improves its waterproof and oil-proof performance. At the same time, by coating modified starch on polyhydroxybutyrate, the compatibility of polyhydroxybutyrate with pulp fiber is improved, thereby ensuring the overall quality of the pulp molded product. At the same time, the modified montmorillonite added can synergistically improve the barrier performance of the pulp molded product with the modified starch-coated polyhydroxybutyrate, thereby jointly improving the waterproof and oil-proof properties of the pulp molded product.

[0030] (2) The degradable, waterproof and oil-proof pulp molded product provided by the present invention has modified starch added as a compatibilizer between polyhydroxybutyrate and pulp fibers. The modified starch has a positive charge and can be tightly combined with the fiber surface with a negative charge, thereby reducing the gaps between the pulp fibers. At the same time, the modified starch has good film-forming properties and strong adhesion to the fibers, and can form a dense film in the pulp film. Together with polyhydroxybutyrate, it can better prevent oily substances from penetrating into the interior of the paper, thereby achieving a better oil-proof effect and ensuring the mechanical properties of the pulp molded product. First, through ball milling treatment, the hydrogen bonding between starch molecules is destroyed under the action of shear force, the starch crystallinity is reduced, and the starch internal energy is increased. Thereby improving the reaction activity of starch; subsequently, the pretreated starch is reacted with 2,3-epoxypropyltrimethylammonium chloride to introduce quaternary ammonium salt into starch, thereby improving the adhesion performance of starch ions to pulp fibers; finally, the cationic starch is reacted with succinic anhydride to introduce hydrophobic alkyl groups on the starch to improve the hydrophobicity of the starch; this method introduces hydrophilic groups and hydrophobic groups into starch respectively through two-step reactions to obtain modified starch. Compared with the simultaneous introduction of hydrophilic groups and hydrophobic groups, the properties of starch derivatives can be changed by adjusting the contents of hydrophilic groups and hydrophobic groups, thereby improving the bonding strength of starch to pretreated polyhydroxybutyrate and pulp fibers, thereby improving the mechanical properties of pulp molded products.

[0031] (3) The modified montmorillonite added to the biodegradable, waterproof and oil-proof pulp molded product provided by the present invention has a layered structure that, when mixed with pulp, can form a circuitous path to prevent oil penetration, thereby improving the oil and water resistance of the pulp molded product; firstly, the montmorillonite is intercalated with hexadecyltrimethylammonium bromide, which can increase the compatibility between the montmorillonite and the pulp fiber on the one hand, and increase the interlayer spacing of the montmorillonite on the other hand, thereby increasing the degree of montmorillonite exfoliation from the pulp fiber, and the increased interlayer spacing is conducive to the subsequent reaction; then, the ethylene is added to the ethylene Triethoxysilane reacts with the composite montmorillonite, which, on the one hand, improves the dispersibility of the montmorillonite, and on the other hand, the introduced silane group can also improve the hydrophobicity and oleophobicity of the montmorillonite; then 10-undecene-1-ol is introduced into the composite montmorillonite through a double bond addition reaction. 10-undecene-1-ol contains a long-chain alkyl group, which further improves the waterproof performance of the pulp molded product; the modified montmorillonite and the modified starch-coated polyhydroxybutyrate work together to prevent the invasion of external liquid water and oil substances, and significantly improve the waterproof and oil-proof performance of the pulp molded product. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] In the present invention, the polyhydroxybutyrate is Dow 3020M; the starch is corn starch; and the particle size of the montmorillonite is 40-60 μm.

[0034] Example 1

[0035] A method for preparing a degradable, waterproof and oil-proof pulp molded product comprises the following steps:

[0036] S1. Pulverize polyhydroxybutyrate to obtain polyhydroxybutyrate powder with a particle size of 20-30 μm, then add 100 g of the polyhydroxybutyrate powder into 1 L of a 1.3 mol / L sodium hydroxide solution, and immerse it at 55° C. for 1.5 h. After the treatment, filter, wash, and dry to obtain pretreated polyhydroxybutyrate;

[0037] S2, the starch was ball-milled at a speed of 3500r / min for 40min to obtain pretreated starch; 90g of the pretreated starch was added to 1L of a sodium hydroxide solution with a concentration of 0.9mol / L, and the mixture was immersed at 45°C for 350min. After the treatment, 10g of 2,3-epoxypropyltrimethylammonium chloride was added, and the mixture was reacted at 65°C for 7h. After the reaction, anhydrous ethanol was added for precipitation, and the mixture was washed with anhydrous ethanol and dried to obtain a solid product; then 90g of the solid product was added to 1L of DMF, followed by the addition of 10g of succinic anhydride and 45g of triethylamine, and the mixture was stirred at 75°C for 5h. After the reaction was completed, the mixture was filtered, washed and dried to obtain a modified starch;

[0038] S3, adding 55g of the modified starch in step S2 to 1L of deionized water, then adding 180g of the pretreated polyhydroxybutyrate in step S1, stirring at 65°C for 2.5h, then vacuum evaporating at 15kpa to remove the deionized water, to obtain modified starch-coated polyhydroxybutyrate;

[0039] S4, 55g of montmorillonite was added to 800mL of deionized water, followed by 8g of hexadecyltrimethylammonium bromide, and the mixture was reacted at 75°C for 4h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a composite montmorillonite; 55g of the composite montmorillonite was added to 900mL of ethanol aqueous solution (the volume ratio of ethanol to water was 3:1), followed by 7g of vinyltriethoxysilane, and the mixture was reacted at 65°C for 1.5h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a vinyl composite montmorillonite; 55g of the vinyl composite montmorillonite was added to 800mL of N,N-dimethylformamide, followed by 6g of 10-undecene-1-ol and 0.3g of azobisisobutyronitrile, and the mixture was reacted at a constant temperature of 85°C for 3h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a modified montmorillonite;

[0040] S5. After soaking the waste corrugated cardboard in water, introduce it into a pulper barrel for pulping for 25 minutes to prepare a pulp suspension with a solid content of 13%. Subsequently, 55g of modified starch-coated polyhydroxybutyrate in step S3, 35g of modified montmorillonite in step S4, 5g of carboxymethyl cellulose, and 8g of Span-80 are added to 1000g of the pulp suspension for mixing and pulping. The stirring speed is 180r / min, the temperature is 70°C, and the stirring time is 1.5h to obtain a mixed slurry, which is then introduced into a mold, filtered through a pulp molding machine to a solid content of 53%, extruded at a pressure of 10MPa, and then demolded to obtain a pulp molded wet blank. The pulp molded wet blank is then placed in a drying oven, dried at 85°C for 4.5h, and placed in a flat vulcanizer for hot pressing at 105°C and 9MPa for 6min to obtain the biodegradable, waterproof and oil-proof pulp molded product.

[0041] Example 2

[0042] A method for preparing a degradable, waterproof and oil-proof pulp molded product comprises the following steps:

[0043] S1. Pulverize polyhydroxybutyrate to obtain polyhydroxybutyrate powder with a particle size of 20-30 μm, then add 100 g of the polyhydroxybutyrate powder into 1 L of a 1.2 mol / L sodium hydroxide solution, and immerse it at 55° C. for 1.5 h. After the treatment, filter, wash, and dry to obtain pretreated polyhydroxybutyrate;

[0044] S2, the starch was ball-milled at a speed of 3500r / min for 40min to obtain pretreated starch; 90g of the pretreated starch was added to 1L of a sodium hydroxide solution with a concentration of 0.6mol / L, and the mixture was immersed at 45°C for 35min. After the treatment, 9g of 2,3-epoxypropyltrimethylammonium chloride was added, and the mixture was reacted at 65°C for 7h. After the reaction, anhydrous ethanol was added for precipitation, and the mixture was washed with anhydrous ethanol and dried to obtain a solid product; then 90g of the solid product was added to 1L of DMF, followed by adding 9g of succinic anhydride and 45g of triethylamine, and the mixture was stirred at 75°C for 5h. After the reaction was completed, the mixture was filtered, washed and dried to obtain a modified starch;

[0045] S3, adding 55g of the modified starch in step S2 to 1L of deionized water, then adding 170g of the pretreated polyhydroxybutyrate in step S1, stirring at 65°C for 25h, then vacuum evaporating at 15kPa to remove the deionized water, to obtain modified starch-coated polyhydroxybutyrate;

[0046] S4, 55g of montmorillonite was added to 800mL of deionized water, followed by 7g of hexadecyltrimethylammonium bromide, and the mixture was reacted at 75°C for 4h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a composite montmorillonite; 55g of the composite montmorillonite was added to 900mL of ethanol aqueous solution (the volume ratio of ethanol to water was 3:1), followed by 6g of vinyltriethoxysilane, and the mixture was reacted at 65°C for 1.5h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a vinyl composite montmorillonite; 55g of the vinyl composite montmorillonite was added to 800mL of N,N-dimethylformamide, followed by 5g of 10-undecene-1-ol and 0.3g of azobisisobutyronitrile, and the mixture was reacted at a constant temperature of 85°C for 3h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a modified montmorillonite;

[0047] S5. After soaking the waste corrugated cardboard in water, introduce it into a pulper barrel for pulping for 25 minutes to prepare a pulp suspension with a solid content of 12%. Subsequently, 55g of modified starch-coated polyhydroxybutyrate in step S3, 35g of modified montmorillonite in step S4, 4g of sodium hexamethyl phosphate, and 7g of Span-80 are added to 1000g of the pulp suspension for mixing and pulping. The stirring speed is 170r / min, the temperature is 70°C, and the stirring time is 1.5h to obtain a mixed slurry, which is then introduced into a mold, filtered through a pulp molding machine to a solid content of 52%, extruded at a pressure of 10MPa, and then demolded to obtain a pulp molded wet blank. The pulp molded wet blank is then placed in a drying oven, dried at 85°C for 4.5h, and placed in a flat vulcanizer for hot pressing at 105°C and 8MPa for 7min to obtain the biodegradable, waterproof and oil-proof pulp molded product.

[0048] Example 3

[0049] A method for preparing a degradable, waterproof and oil-proof pulp molded product comprises the following steps:

[0050] S1. Pulverize polyhydroxybutyrate to obtain polyhydroxybutyrate powder with a particle size of 20-30 μm, then add 100 g of the polyhydroxybutyrate powder into 1 L of 1 mol / L sodium hydroxide solution, and immerse at 50° C. for 2 h. After the treatment, filter, wash, and dry to obtain pretreated polyhydroxybutyrate;

[0051] S2, ball milling the starch at a speed of 3500r / min for 40min to obtain pretreated starch; adding 80g of the pretreated starch to 1L of a sodium hydroxide solution with a concentration of 0.5mol / L, immersing at 40°C for 40min, adding 8g of 2,3-epoxypropyltrimethylammonium chloride after the treatment, reacting at 60°C for 8h, adding anhydrous ethanol for precipitation after the reaction, washing with anhydrous ethanol, and drying to obtain a solid product; then adding 80g of the solid product to 1L of DMF, followed by adding 8g of succinic anhydride and 40g of triethylamine, stirring and reacting at 70°C for 6h, filtering, washing, and drying after the reaction to obtain modified starch;

[0052] S3, adding 50g of the modified starch in step S2 to 1L of deionized water, then adding 150g of the pretreated polyhydroxybutyrate in step S1, stirring at 60°C for 3h, and then performing vacuum rotary evaporation at 10kPa to remove the deionized water to obtain modified starch-coated polyhydroxybutyrate;

[0053] S4, add 50g of montmorillonite to 800mL of deionized water, then add 6g of hexadecyltrimethylammonium bromide, react at 70°C for 5h, filter, wash and dry after the reaction is completed to obtain composite montmorillonite; add 50g of composite montmorillonite to 900mL of ethanol aqueous solution (the volume ratio of ethanol to water is 3:1), then add 5g of vinyltriethoxysilane, react at 60°C for 2h, filter, wash and dry after the reaction is completed to obtain vinyl composite montmorillonite; add 50g of vinyl composite montmorillonite to 800mL of N,N-dimethylformamide, then add 4.5g of 10-undecene-1-ol and 0.2g of azobisisobutyronitrile, react at 80°C for 4h, filter, wash and dry after the reaction is completed to obtain modified montmorillonite;

[0054] S5. After soaking the waste corrugated cardboard in water, introduce it into a pulper barrel for pulping for 20 minutes to prepare a pulp suspension with a solid content of 10%. Subsequently, 50g of the modified starch-coated polyhydroxybutyrate in step S3, 30g of the modified montmorillonite in step S4, 3g of sodium dodecylbenzene sulfonate, and 5g of Span-80 are added to 1000g of the pulp suspension for mixing and pulping. The stirring speed is 150r / min, the temperature is 60°C, and the stirring time is 1h to obtain a mixed slurry, which is then introduced into a mold, filtered through a pulp molding machine to a solid content of 50%, extruded at a pressure of 5MPa, and then demolded to obtain a pulp molded wet blank. The pulp molded wet blank is then placed in a drying oven, dried at 80°C for 5h, and placed in a flat vulcanizer for hot pressing at 100°C and 7MPa for 8min to obtain the degradable, waterproof and oil-proof pulp molded product.

[0055] Example 4

[0056] A method for preparing a degradable, waterproof and oil-proof pulp molded product comprises the following steps:

[0057] S1. Pulverize polyhydroxybutyrate to obtain polyhydroxybutyrate powder with a particle size of 20-30 μm, then add 100 g of the polyhydroxybutyrate powder into 1 L of a 1.5 mol / L sodium hydroxide solution, and immerse at 60° C. for 1 h. After the treatment, filter, wash, and dry to obtain pretreated polyhydroxybutyrate;

[0058] S2, ball milling the starch at a speed of 3500r / min for 40min to obtain pretreated starch; adding 100g of the pretreated starch to 1L of a sodium hydroxide solution with a concentration of 0.8mol / L, immersing at 50°C for 30min, adding 12g of 2,3-epoxypropyltrimethylammonium chloride after the treatment, reacting at 70°C for 6h, adding anhydrous ethanol to precipitate after the reaction, washing with anhydrous ethanol, and drying to obtain a solid product; then adding 100g of the solid product to 1L of DMF, followed by adding 12g of succinic anhydride and 50g of triethylamine, stirring and reacting at 80°C for 4h, filtering, washing, and drying after the reaction to obtain modified starch;

[0059] S3, adding 60g of the modified starch in step S2 to 1L of deionized water, then adding 200g of the pretreated polyhydroxybutyrate in step S1, stirring at 70°C for 2h, and then vacuum evaporating at 20kPa to remove the deionized water to obtain modified starch-coated polyhydroxybutyrate;

[0060] S4, add 60g of montmorillonite to 800mL of deionized water, then add 9g of hexadecyltrimethylammonium bromide, react at 80°C for 3h, filter, wash and dry after the reaction is completed to obtain composite montmorillonite; add 60g of composite montmorillonite to 900mL of ethanol aqueous solution (the volume ratio of ethanol to water is 3:1), then add 8g of vinyltriethoxysilane, react at 70°C for 1h, filter, wash and dry after the reaction is completed to obtain vinyl composite montmorillonite; add 60g of vinyl composite montmorillonite to 800mL of N,N-dimethylformamide, then add 7g of 10-undecene-1-ol and 0.4g of azobisisobutyronitrile, react at a constant temperature of 90°C for 2h, filter, wash and dry after the reaction is completed to obtain modified montmorillonite;

[0061] S5. After soaking the waste corrugated cardboard in water, introduce it into a pulper barrel for pulping for 30 minutes to prepare a pulp suspension with a solid content of 15%. Subsequently, 60g of the modified starch-coated polyhydroxybutyrate in step S3, 40g of the modified montmorillonite in step S4, 6g of carboxymethyl cellulose, and 10g of Span-80 are added to 1000g of the pulp suspension for mixing and pulping. The stirring speed is 200r / min, the temperature is 80°C, and the stirring time is 2h to obtain a mixed slurry, which is then introduced into a mold, filtered through a pulp molding machine to a solid content of 55%, extruded at a pressure of 15MPa, and then demolded to obtain a pulp molded wet blank. The pulp molded wet blank is then placed in a drying oven, dried at 90°C for 4h, and placed in a flat vulcanizer for hot pressing at 110°C and 10MPa for 5min to obtain the biodegradable, waterproof and oil-proof pulp molded product.

[0062] Comparative Example 1

[0063] A method for preparing a degradable, waterproof and oil-proof pulp molded product comprises the following steps:

[0064] S1. Pulverize polyhydroxybutyrate to obtain polyhydroxybutyrate powder with a particle size of 20-30 μm, then add 100 g of the polyhydroxybutyrate powder into 1 L of a 1.3 mol / L sodium hydroxide solution, and immerse it at 55° C. for 1.5 h. After the treatment, filter, wash, and dry to obtain pretreated polyhydroxybutyrate;

[0065] S2, adding 55g of starch in step S1 to 1L of deionized water, then adding 180g of pretreated polyhydroxybutyrate in step S1, stirring at 65°C for 2.5h, then performing vacuum rotary evaporation at 15kpa to remove deionized water, to obtain starch-coated polyhydroxybutyrate;

[0066] S3, 55g of montmorillonite was added to 800mL of deionized water, followed by 8g of hexadecyltrimethylammonium bromide, and the mixture was reacted at 75°C for 4h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a composite montmorillonite; 55g of the composite montmorillonite was added to 900mL of ethanol aqueous solution (the volume ratio of ethanol to water was 3:1), followed by 7g of vinyltriethoxysilane, and the mixture was reacted at 65°C for 1.5h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a vinyl composite montmorillonite; 55g of the vinyl composite montmorillonite was added to 800mL of N,N-dimethylformamide, followed by 6g of 10-undecene-1-ol and 0.3g of azobisisobutyronitrile, and the mixture was reacted at a constant temperature of 85°C for 3h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain a modified montmorillonite;

[0067] S4, after soaking the waste corrugated cardboard in water, introduce it into a pulper barrel for pulping, and beat it for 25 minutes to prepare a pulp suspension with a solid content of 13%. Subsequently, 55g of starch-coated polyhydroxybutyrate in step S3, 35g of modified montmorillonite in step S4, 5g of carboxymethyl cellulose, and 8g of Span-80 are added to 1000g of the pulp suspension for mixing and beating. The stirring speed is 180r / min, the temperature is 70°C, and the stirring time is 1.5h to obtain a mixed slurry, which is then introduced into a mold, filtered through a pulp molding machine to a solid content of 53%, extruded at a pressure of 10MPa, and then demolded to obtain a pulp molded wet blank. The pulp molded wet blank is then placed in a drying oven, dried at 85°C for 4.5h, and placed in a flat vulcanizer for hot pressing at 105°C and 9MPa for 6min to obtain the biodegradable, waterproof and oil-proof pulp molded product.

[0068] Compared with Example 1, the starch was not modified in this comparative example.

[0069] Comparative Example 2

[0070] A method for preparing a degradable, waterproof and oil-proof pulp molded product comprises the following steps:

[0071] S1. Pulverize polyhydroxybutyrate to obtain polyhydroxybutyrate powder with a particle size of 20-30 μm, then add 100 g of the polyhydroxybutyrate powder into 1 L of a 1.3 mol / L sodium hydroxide solution, and immerse it at 55° C. for 1.5 h. After the treatment, filter, wash, and dry to obtain pretreated polyhydroxybutyrate;

[0072] S2, the starch was ball-milled at a speed of 3500r / min for 40min to obtain pretreated starch; 90g of the pretreated starch was added to 1L of a sodium hydroxide solution with a concentration of 0.9mol / L, and the mixture was immersed at 45°C for 350min. After the treatment, 10g of 2,3-epoxypropyltrimethylammonium chloride was added, and the mixture was reacted at 65°C for 7h. After the reaction, anhydrous ethanol was added for precipitation, and the mixture was washed with anhydrous ethanol and dried to obtain a solid product; then 90g of the solid product was added to 1L of DMF, followed by the addition of 10g of succinic anhydride and 45g of triethylamine, and the mixture was stirred at 75°C for 5h. After the reaction was completed, the mixture was filtered, washed and dried to obtain a modified starch;

[0073] S3, adding 55g of the modified starch in step S2 to 1L of deionized water, then adding 180g of the pretreated polyhydroxybutyrate in step S1, stirring at 65°C for 2.5h, then vacuum evaporating at 15kpa to remove the deionized water, to obtain modified starch-coated polyhydroxybutyrate;

[0074] S4, adding 55g of montmorillonite to 800mL of deionized water, and then adding 8g of hexadecyltrimethylammonium bromide, reacting at 75°C for 4h, filtering, washing and drying after the reaction is completed to obtain a composite montmorillonite;

[0075] S5. After soaking the waste corrugated cardboard in water, introduce it into a pulper barrel for pulping for 25 minutes to prepare a pulp suspension with a solid content of 13%. Subsequently, 50-60g of the modified starch-coated polyhydroxybutyrate in step S3, 35g of the composite montmorillonite in step S4, 5g of carboxymethyl cellulose, and 8g of Span-80 are added to 1000g of the pulp suspension for mixing and pulping. The stirring speed is 180r / min, the temperature is 70°C, and the stirring time is 1.5h to obtain a mixed slurry, which is then introduced into a mold, filtered through a pulp molding machine to a solid content of 53%, extruded at a pressure of 10MPa, and then demolded to obtain a pulp molded wet blank. The pulp molded wet blank is then placed in a drying oven, dried at 85°C for 4.5h, and placed in a flat vulcanizer for hot pressing at 105°C and 9MPa for 6min to obtain the biodegradable, waterproof and oil-proof pulp molded product.

[0076] Compared with Example 1, in this comparative example, the composite montmorillonite was not subjected to reaction with vinyltriethoxysilane and 10-undecene-1-ol.

[0077] The pulp molded products prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to performance tests, as follows: Water contact angle measurement: The pulp molded samples were fixed on a glass slide with double-sided tape, and the dynamic contact angle of 2-5 min was tested using a contact angle meter. Five samples were measured for each sample and the average value was taken; the tensile strength was tested according to GB / T 12914-2018 "Determination of tensile strength of paper and paperboard-Constant rate stretching method", the sampling direction was longitudinal, the sample size was 250 mm×15 mm, the stretching speed was 20 mm / min, and the samples were placed in an environment with a temperature of 23°C and a relative humidity of 50% for 24 h before the test; Oil resistance test: The oil and grease resistance grade determination method adopted the TAPPI T 559cm-02 standard, specifically: 12 test solutions (numbered 1-12) were prepared with a series of castor oil, toluene and n-heptane in different volume ratios, and then the oil and grease resistance of the food packaging paper was determined using these 12 test solutions with different surface tensions. During the test, drop the test liquid onto the surface of the pulp molding material sample from 25mm (1inch). After 15s, gently wipe off the remaining test liquid with absorbent cotton and immediately observe whether the pulp molding has any penetration. Repeat the test until the food packaging paper surface of the numbered test liquid is not penetrated and changes color. The oil resistance of the pulp molding product is the value of the number. The higher the oil resistance grade of the oil-proof paper, the stronger the oil resistance of the pulp molding and the better the practicality.

[0078] Table 1 Performance test results of each group of pulp molded products

[0079] Group <![CDATA[Grammage g / m 2 > Tensile strength(kN / m) Water contact angle (°) Oil resistance grade Example 1 863 24.81 132 11 Example 2 855 23.94 129 10 Example 3 831 23.15 125 9 Example 4 879 25.07 128 10 Comparative Example 1 868 19.25 104 7 Comparative Example 2 857 21.43 93 9

[0080] It can be seen from Table 1 above that the pulp molded product prepared by the present invention has good hydrophobicity and oil resistance, and also has good tensile strength, and has good application prospects.

[0081] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a degradable, waterproof and oil-proof pulp molded product, characterized in that: The following steps are involved: S1, crushing polyhydroxybutyrate to obtain micro-nano polyhydroxybutyrate powder, then adding the polyhydroxybutyrate powder into a sodium hydroxide solution for immersion treatment, filtering, washing and drying after the treatment to obtain pretreated polyhydroxybutyrate; S2, ball milling the starch to obtain pretreated starch; The pretreated starch is added to a sodium hydroxide solution for immersion treatment, and after the treatment is completed, 2,3-epoxypropyltrimethylammonium chloride is added to carry out an etherification reaction, and after the reaction is completed, anhydrous ethanol is added for precipitation, and the solid product is washed and dried to obtain a solid product; then the solid product is added to DMF, and then succinic anhydride and triethylamine are added to carry out stirring reaction, and after the reaction is completed, the modified starch is filtered, washed and dried to obtain a modified starch; S3, adding the modified starch in step S2 into deionized water, and then adding the pretreated polyhydroxybutyrate in step S1, stirring, and then performing reduced pressure rotary evaporation to obtain modified starch-coated polyhydroxybutyrate; S4, adding montmorillonite to deionized water, then adding hexadecyltrimethylammonium bromide, stirring for reaction, filtering, washing, and drying after the reaction is completed to obtain composite montmorillonite; adding composite montmorillonite to ethanol aqueous solution, then adding vinyltriethoxysilane, heating for reaction, filtering, washing, and drying after the reaction is completed to obtain vinyl composite montmorillonite; adding vinyl composite montmorillonite to N,N-dimethylformamide, then adding 10-undecene-1-ol and azobisisobutyronitrile, carrying out constant temperature reaction, filtering, washing, and drying after the reaction is completed to obtain modified montmorillonite; S5. After soaking the waste corrugated cardboard in water, introduce it into a pulper barrel for pulping for 20-30 minutes to prepare a pulp suspension with a solid content of 10-15%. Then, add the modified starch-coated polyhydroxybutyrate in step S3, the modified montmorillonite in step S4, a dispersant, and Span-80 to the pulp suspension for mixing and beating to obtain a mixed slurry, which is then introduced into a mold, filtered and extruded by a pulp molding machine, demolded, dried, and hot-pressed to obtain the biodegradable, waterproof, and oil-proof pulp molded product.

2. The preparation method according to claim 1, characterized in that: The particle size of the polyhydroxybutyrate powder in step S1 is 20-30 μm; the concentration of the sodium hydroxide solution is 1-1.5 mol / L, the temperature of the immersion treatment is 50-60° C., and the time is 1-2 h.

3. The preparation method according to claim 1, characterized in that: In step S2, the rotation speed of the ball mill is 3000-4000 r / min, and the time is 30-50 min; the concentration of the sodium hydroxide solution is 0.5-0.8 mol / L, the temperature of the immersion treatment is 40-50° C., and the time is 30-40 min; the mass ratio of the pretreated starch and 2,3-epoxypropyltrimethylammonium chloride is 80-100:8-12, and the temperature of the etherification reaction is 60-70° C., and the time is 6-8 h.

4. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the solid product, succinic anhydride and triethylamine is 80-100:8-12:40-50; the stirring reaction temperature is 70-80° C. and the time is 4-6 hours.

5. The preparation method according to claim 1, characterized in that: In step S3, the mass ratio of the modified starch to the pretreated polyhydroxybutyrate is 50-60:150-200, the stirring temperature is 60-70° C., and the time is 2-3 h.

6. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of montmorillonite to hexadecyltrimethylammonium bromide is 50-60:6-9, the stirring reaction temperature is 70-80°C, and the time is 3-5h; the mass ratio of the composite montmorillonite to vinyltriethoxysilane is 50-60:5-8, the heating reaction temperature is 60-70°C, and the time is 1-2h.

7. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of the vinyl composite montmorillonite, 10-undecene-1-ol and azobisisobutyronitrile is 50-60:4.5-7:0.2-0.4 g, the temperature of the isothermal reaction is 80-90° C., and the time is 2-4 h.

8. The preparation method according to claim 1, characterized in that: In step S5, the mass ratio of the pulp suspension, modified starch-coated polyhydroxybutyrate, modified montmorillonite, dispersant, and Span-80 is 1000:50-60:30-40:3-6:5-10; the dispersant is one or more of carboxymethyl cellulose, sodium hexamethyl phosphate, and sodium dodecylbenzene sulfonate.

9. The preparation method according to claim 1, characterized in that: In step S5, the mixed slurry is filtered to a solid content of 50-55%, and then demolded after extrusion molding at a pressure of 5-15 MPa to obtain a pulp molded wet blank. The pulp molded wet blank is then placed in a drying oven, dried at 80-90° C. for 4-5 hours, and then transferred to a flat vulcanizer for hot pressing and shaping at 100-110° C. and 7-10 MPa for 5-8 minutes.

10. A biodegradable, waterproof and oil-proof pulp molded product prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Fully-degradable fluoride-free paper pulp molded dinner plate and preparation method thereof

    CN113215862A

  • Paper fiber molding material and preparation method thereof

    CN115821641A

Cited By

  • Composition for manufacturing barrier layer of paper pulp molded product, barrier layer, manufacturing method of barrier layer, material and paper container

    CN120367073A